1977
DOI: 10.1099/00221287-101-2-227
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of Bacillus Spores in Dry Systems at Low and High Temperatures

Abstract: A plot of the thermal resistance of Bacillus subtilis var. niger spores (log D value) against temperature was linear between 37 and 190 "C (z = 23 "C), provided that the relative humidity of the spore environment was kept below a certain critical level. The corresponding plot for Bacillus stearothermophilus spores was linear in the range 150 to 180 "C (z = 29 "C) but departed from linearity at lower temperatures (decreasing z value). However, the z value of 29 "C was decreased to 23 "C if spores were dried bef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

1978
1978
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 7 publications
1
4
0
Order By: Relevance
“…Similarly the z-value (var.niger) obtained by various workers using TGE range from 12.9"C to 32°C compared with 21.25"C obtained by our methods (Table 8). The z-value graphs are linear (Figs 6 and 7) and in good agreement with those published by Molin (19776) using the same temperature range. Molin & Ostlund (1976) have shown that spore density affects the rate of kill of spores dried on to glass surfaces heated by infra-red radiation and this is an additional cause of variation between dry-heat killing data.…”
Section: Minutessupporting
confidence: 87%
“…Similarly the z-value (var.niger) obtained by various workers using TGE range from 12.9"C to 32°C compared with 21.25"C obtained by our methods (Table 8). The z-value graphs are linear (Figs 6 and 7) and in good agreement with those published by Molin (19776) using the same temperature range. Molin & Ostlund (1976) have shown that spore density affects the rate of kill of spores dried on to glass surfaces heated by infra-red radiation and this is an additional cause of variation between dry-heat killing data.…”
Section: Minutessupporting
confidence: 87%
“…More importantly, plasmas still provide reactive gases to downstream surfaces for solid or thickened agents that do not evaporate readily. This is of particular importance in the case of biological agents such as anthrax, which would require many days to be neutralized solely by the combination of vacuum and heat at temperatures below 70 C [18]. Hence, this technology has significant advantages over infrared-heated, vacuum-based decon.…”
Section: Evaporation Of Agentmentioning
confidence: 99%
“…Finally, the fourth barrier is pasteurization or drying of the SCP to produce a final bio-product. 140 Future research must provide evidence that these multiple barriers ensure compliance to feed and safety regulations. Eventually, these evidence must lead to further amendments of current legislation such as the EC Directive 82/471/EEC concerning products used in animal nutrition.…”
Section: Ensuring Product Quality and Safetymentioning
confidence: 99%
“…However, to the authors’ knowledge no similar parameters to produce AHB selectively are available today. Finally, the fourth barrier is pasteurization or drying of the SCP to produce a final bioproduct . Future research must provide evidence that these multiple barriers ensure compliance to feed and safety regulations.…”
Section: Sewage-to-commodities: Challenges Opportunities and Prospectsmentioning
confidence: 99%